Underutilised Resources in Urban Environments - Kusch-Brandt, Sigrid (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is the result of a Special Issue of the journal Resources. The Special Issue was initiated to identify promising solutions and specific challenges in the context of underused resources in urban environments. Authors focus on two main areas: the establishment of circular economy schemes based on valorizing wastes that occur in urban areas and the exploitation of renewable energies. The circular economy and renewable resources hold key potential for increasing the sustainability of cities, and the presented studies enhance our understanding of how to unlock this potential. Effective regulatory frameworks and policymaking processes that balance the power between stakeholders are required to successfully manage energy transition and the transition to more circular economies. The positive role of community engagement merits high attention. To recover valuable resources from household waste, a focus on technology and infrastructure is required but is insufficient; motivational factors and knowledge of citizens are the most essential elements. The need to more reliably quantify and better characterize recyclable material streams also evidently remains, especially where population numbers are further growing. This book provides a rich source to explore promising solutions, challenges, and research needed for the sound management of resources in urban settings.